Pragmatic Terminology in the Arabic Linguistic Heritage Through Masʿūd Ṣaḥrāwī’s Pragmatics among Arab Scholars (“Intentionality” as a Case Study) (Journal of Informatics Education and Research, 2026)
Through his book entitled Pragmatics According to Arab Scholars: A Pragmatic Study of the Phenomenon of Speech Acts in the Arabic Linguistic Heritage, Masʿūd Ṣaḥrāwī sought to reread the Arabic intellectual tradition by drawing upon the most significant concepts of modern pragmatics. This endeavor reflects his conviction regarding the importance of establishing a connection between contemporary linguistics and the Arabic linguistic heritage, while at the same time respecting the distinctive characteristics of the latter.